Optimum Cycle Time Based On Jig And Workstation Design Combinations - Nabilah, Mohd Safar (2010)
Jig design and workstation design are areas that influence productivity. Good combination of jig and workstation design is needed to obtain optimum cycle time. The best combination also helps workers to perform their job faster and easier and thus, enhance the productivity. This project determines the most significant combination of jig design and workstation design in assembly line of plug. The first step of the study was to determine the factors that influence the productivity; in this case they were the assembly time of electrical appliances which are BS 1363 plugs. The second step was to determine the level of each factor and then design for fu ll factorial experiments. There were three factors being evaluated for their influence on assembly time of plug i.e. number of plug per jig, shape of jig and assembly position of worker. umber of plug per jig factor has three levels (3, 4 and 5), shape of jig factor has 3 levels (horizontal, vertical and square) and assembly position has two levels (sitting and standing). There were eighteen combinations of experimental runs and each combination was repeated eight times. Therefore, total of 144 experiments were conducted for this project. ANOV A was used to identify the optimum combination. The result shows that the lowest average of assembly time is obtained at combination of five plugs per jig, square jig shape and sitting position.